Historical Dictionary of Golf - Mallon, Bill; Jerris, Randon (Rowman & Littlefield Publishers, 2011)
Golf has been called the greatest of all games, but it has also been derided by none other than Mark Twain as nothing more than a good walk spoiled. Traditional teaching holds that golf originated in Scotland around the 15th century. However, there is historical evidence of games similar to golf being played in the low countries of Europe back in the 13th century. Over the many centuries of golf's evolution, the balls used have changed greatly, as have the clubs, the holes, the courses, and the entire game itself. The Historical Dictionary of Golf presents a comprehensive history of the game through a chronology, an introductory essay, a bibliography, photos, and over 300 cross-referenced dictionary entries on places, teams, terminology, and people, including Arnold Palmer, Greg Norman, Lee Trevino, Jack Nicklaus, Annika Sörenstam, Lorena Ochoa, Phil Mickelson, and, of course, Tiger Woods. Appendixes of the members of the World Golf Hall of Fame, the Major Championships of Golf, the International Team Events, and the Professional Tour Awards are also included.